Corporate Governance dan Audit Quality Sebagai Pendeteksi Earning Management Perusahaan Pada Saat IPO - Hutami, Sri (STIE Surakarta, 2014)
This paper examines thecorporate governance, audit quality,can to detectthe earning management when initial public offering happens to the company in Indonesian Stock Exchange. Coporate governance is represented by board of directors, managerial ownership and the existence of audit committee. Audit quality is represented by a auditors which does audit to the emiten financial report. The big auditors is represented by a Big Four Auditorâs and a small auditorsis non-Big Four Auditorâs. This research uses secondary data from prospectus of the company and the short prospectus publised by Indonesian Stock Exchange. The result of this research can prove that the existence of committee audit can decrease earning management practice, while other variables are board of directors is significant positive associated with earnigs management. two variable proved did not influence earning managementpractic is managerial ownership and size KAP. The implementation of corporate governance should be able to decrease earning management practice but the fact that it has not had effective effect when Initial Public Offering happens to the company